Effect of cimicifuga racemosa on menopausal syndrome caused by LHRH-a in breast cancer. (28th June 2019) - Wang, Chen; Huang, Qiang; Liang, Chen-Lu; Zhang, Yi-Wen; Deng, De-Hou; Yu, Yang; Chen, Dao-Bao; Yang, Hong-Jian; Yu, Xing-Fei
Abstract: Ethnopharmacological relevance: Cimicifuga racemose is previously proved effective on nature menopausal syndrome (MPS). However, its clinical value in treating with MPS induced by luteinizing-hormone releasing hormone analogue (LHRH-a) therapy of pre-/peri-menopausal breast cancer patients is still unknown. Aim of study: This perspective randomised-design study is to investigate the effect and safety of cimicifuga racemosa on MPS induced by LHRH-a in breast cancer (clinical trial registered: NCT03339882 ). Materials and methods: Breast cancer patients planning for LHRH-a treatment were randomly divided into 2 groups. The control group which was being treated with the standard treatment of LHRH-a. The other group was being treated with Remifemin, the commercialized product of cimicifuga racemose extract, combined with LHRH-a, called Remifemin group. Our main endpoint was Kupperman menopause index (KMI). Hormone levels in peripheral blood and gynecological complications were also evaluated. Results: Totally, 85 patients (42 in Remifemin group and 43 in control group) were enrolled in Zhejiang Cancer Hospital. At the 4th, 8th and 12th week after using LHRH-a, the KMI were all significantly lower in Remifemin group than in control group ( P  < 0.01), while the hormone levels, including estradiol (E2 ), follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were similar in the two groups. In addition, the incidence of cervical cyst in Remifemin group was higher than that in control group ( P  = 0.02), and there was no significant difference in the other gynecological complications, including endometrial thickening, ovarian cyst or uterine fibroid ( P  > 0.05). Conclusions: Cimicifuga racemose is effective, oncological safe and reliable for treatment of MPS caused by LHRH-a in breast cancer. Graphical abstract: Image 1